The Influence of Service Quality, Price Congruence, and Product Innovation on Customer Satisfaction at WCB Coffee Shop - Nony Kezia Marchyta; Joshua Ryan Suhianto; Clarissa Listya Susilo (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Purpose – This study aims to examine how service quality, price congruence, and product innovation contribute to customer satisfaction at WCB Coffee Shop in Central Java, particularly in the context of declining weekend sales, escalating competition, and inconsistent empirical evidence regarding the role of product innovation. Design/methodology/approach – This research employs a quantitative framework. Data were collected from 100 respondents selected through purposive sampling, and the empirical analysis was conducted using multiple linear regression. Finding/Results – Service quality and price congruence exert a significant and positive influence on customer satisfaction, confirming them as the principal drivers of consumer satisfaction. In contrast, product innovation does not show a statistically significant effect, suggesting that patrons prioritize the authenticity of coffee taste over novelty. Together, these three predictors account for 32.6% of the variance in customer satisfaction (R² = 0.326), indicating that other external determinants also play a meaningful role. Originality/Value – This study highlights that in a small-city coffee shop setting, consistent service delivery and fair pricing are more decisive levers of customer satisfaction than product innovation. The findings offer practical guidance for comparable businesses to optimize resource allocation and strategic focus.